Incidencia de los cambios de uso de suelo en la deforestación del sitio Pechichal, cantón Junín-Manabí - Baren Hidalgo, Eulises Ismael (2022)
The present study evaluated the incidence of changes in land use in the Pechichal site, Junín Manabí canton, through the rate of deforestation, in the period 2010 - 2020. The main changes in land use generated in This period of time, through the obtaining of Lanstat images, classification of images in ArcGis, elaboration of maps and evaluation of the rates of change of land use, in addition the rate of deforestation was quantified, and the relationship between the land use change rates on the rate of deforestation. It was shown that the change in land use that suffered a greater increase was cultivated pastures, while population settlements decreased in the decade studied. The quantified deforestation rate was 9.48%, while the relationship between changes in land use and the deforestation rate is positive and growing (p=0.05), indicating that as one variable increases, the other does. simultaneously indicating a degree of incidence of 56.42%. It is concluded that the use of the land in the Pechichal commune has caused an increase in the agricultural frontier promoted directly to the provision of natural resources.